Obstacles to the Implementation of Community Rights in the Drafting of Democratic Village Regulations - Mukhammad Soleh; Dian Utami Ikhwaningrum; Marsudi Dedi Putra; Vivi Fauziatul Aini; Angellica Chirzt Ernestacia (Ilomata International Journal of Social Science, 2026)
The community has the right to express its aspirations, suggestions, and opinions regarding the implementation of village government. The purpose of this study is to analyse the implementation of community rights and identify factors that hinder their implementation in village governance, particularly in the preparation of the Draft Village Regulation, to enhance the implementation of democracy in the Village. The research method employed is empirical legal research, utilising primary and secondary data collection methods through in-depth observations and interviews. The results are based on field studies and documents from the Gunungsari Village Government, Tajinan District, Malang Regency. A qualitative juridical analysis is then carried out. The results of the study indicate that the factors inhibiting the implementation of community rights in expressing aspirations, suggestions, and input in the preparation of the draft village regulation. First, there are still people who do not understand their rights. Second, there are still people who remain indifferent. Third: a lack of socialisation from the village government to the community about the plan to prepare the village regulation.